The Role of Animal Cognition in Human-Wildlife Interactions - Goumas, Madeleine; Lee, Victoria E.; Boogert, Neeltje J.; Kelley, Laura A.; Thornton, Alex (Frontiers in Psychology, 2020)
Humans have a profound effect on the planet’s ecosystems, and unprecedented rates of human population growth and urbanisation have brought wild animals into increasing contact with people. For many species, appropriate responses towards humans are likely to be critical to survival and reproductive success. Although numerous studies have investigated the impacts of human activity on biodiversity and species distributions, relatively few have examined the effects of humans on the behavioural responses of animals during human-wildlife encounters, and the cognitive processes underpinning those responses. Furthermore, while humans often present a significant threat to animals, the presence or behaviour of people may be also associated with benefits, such as food rewards. In scenarios where humans vary in their behaviour, wild animals would be expected to benefit from the ability to discriminate between dangerous, neutral and rewarding people. Additionally, individual differences in cognitive and behavioural phenotypes and past experiences with humans may affect animals’ ability to exploit human-dominated environments and respond appropriately to human cues. In this review, we examine the cues that wild animals use to modulate their behavioural responses towards humans, such as human facial features and gaze direction. We discuss when wild animals are expected to attend to certain cues, how information is used, and the cognitive mechanisms involved. We consider how the cognitive abilities of wild animals are likely to be under selection by humans and therefore influence population and community composition. We conclude by highlighting the need for long-term studies on free-living, wild animals to fully understand the causes and ecological consequences of variation in responses to human cues. The effects of humans on wildlife behaviour are likely to be substantial, and a detailed understanding of these effects is key to implementing effective conservation strategies and managing human-wildlife conflict.